Occult Dysplasia in a Localized Giant Pseudopolyp in Crohn’s Colitis: A Case Report - Jonathan Wyse; Esther Lamoureux; Philip H Gordon; Alain Bitton (Canadian Journal of Gastroenterology)
Localized giant pseudopolyposis of the colon (pseudopolyp larger than 1.5 cm in size) is a rare complication of inflammatory bowel disease. There is one report of an occult carcinoma within such a lesion, and no reports of sole dysplasia. A case of a 42-year-old man with longstanding Crohn’s colitis who underwent a colonoscopy revealing a large, multilobulated mass at the splenic flexure that was not amenable to endoscopic removal, is described. Multiple biopsies showed no dysplasia and histology was consistent with an inflammatory pseudopolyp. Computed tomographic colonography demonstrated a mass resembling a large villous tumour. A decision for surgery was made. The surgical specimen was a complex anastomosing inflammatory pseudopolyp 5 cm × 4 cm × 3 cm in size, with a focus of low-grade dysplasia in an area free of inflammation.